1983
DOI: 10.1177/014107688307601108
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Analysis of Laryngeal Trauma Secondary to Intubation

Abstract: Summary: A study was undertaken to analyse the effect of short-term intubation on the voice. Children were examined laryngographically both pre-and postoperatively. Changes in larynx frequency distribution following intubation were documented using the technique of electrolaryngography; the resolution of these changes was similarly recorded. The results, in comparison with the frequency distributions associated with other disease states, give insight into the nature of the damage and its effect on vocal fold v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 20 publications
0
10
1
Order By: Relevance
“…The results indicated a significant decrease in the mean fundamental frequency, standard deviation of F 0 , and harmonic to noise ratio together with a significant increase in shimmer and jitter. On the other hand, Gleeson and many others 10,23 have shown a consistent increase in F 0 after intubation. Yonick et al conducted a study on 13 male subjects undergoing cardiac surgery and found nonsignificant changes in the mean fundamental frequency F 0 , standard deviation, mean sound pressure level, and sound pressure level standard deviation.…”
Section: Discussionmentioning
confidence: 75%
“…The results indicated a significant decrease in the mean fundamental frequency, standard deviation of F 0 , and harmonic to noise ratio together with a significant increase in shimmer and jitter. On the other hand, Gleeson and many others 10,23 have shown a consistent increase in F 0 after intubation. Yonick et al conducted a study on 13 male subjects undergoing cardiac surgery and found nonsignificant changes in the mean fundamental frequency F 0 , standard deviation, mean sound pressure level, and sound pressure level standard deviation.…”
Section: Discussionmentioning
confidence: 75%
“…Therefore, monitoring with a pulse oximeter and oxygen supplementation when postoperative Sp02 falls to<%% are recommended guidelines (DeSoto et al 1988;Cote et al 1992) and are used at our institution. There is an increased risk with tracheal intubation in patients with URTI which can also lead to severe complications (Gleeson & Fourcin 1983;Olsson & Hallen 1984;Black, Hatch & Nauth-Nisir 1990). Conversely, general anaesthesia without tracheal intubation in a patient with URTI does not increase the frequency of laryngospasm when compared with normal children (Tait & Knight 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Tracheal intubation (TT) is usually performed (Montgomery, Watson & Mackie 1987;Facer 1989). However, different types of complications such as laryngeal spasm (Olsson & Hallen 1984), laryngeal trauma (Gleeson & Fourcin 1983) or post extubation stridor (Black, Hatch & Nauth-Misir 1990) may occur. The laryngeal mask airway (LMA) which does not interfere with the laryngotracheal tract is now commonly used in general paediatric surgery (Mason & Bingham 1990;Fawcett, Ravilia & Radford 1991) as well as in some ENT procedures (Johnston et ai.…”
Section: Introductionmentioning
confidence: 99%
“…Less severe acute injuries to the larynx after tracheal intubation have been described in terms of voice changes ( 10) and laryngographic frequency distribution ( 11). However, laryngoscopic studies of appearances after short鈥恡erm tracheal intubation have failed to reveal consistent abnormalities in laryngeal mucosa ( 12).…”
Section: Discussionmentioning
confidence: 99%